On Basic Semiconductor Equations with Heat Conduction (Journal of Partial Differential Equations, 1995)
We prove the global existence of solution to basic semiconductor equations with heat conduction; If the domain is narrow in one direction, then the basic equations has a unique steady-state which is locally asymptotically stable.
Keywords: Super-subsolution; fixed point theorem; L^P estimate and Schauder estimate